2016
DOI: 10.1186/s13584-016-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

Perception of primary care physicians on the impact of comprehensive geriatric assessment: what is the next step?

Abstract: Older adults are at high risk of developing multimorbidity, and the high levels of clinical and psychosocial complexity in this population pose special challenges for primary care physicians (PCPs). As a way to improve the care for the older adults, a number of health systems have developed programs to provide comprehensive geriatric assessment (CGA), which generally refers to an intensive interprofessional evaluation and management of geriatric syndromes with the goals of maximizing health in aging. Sternberg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Similar to our findings, Darby et al reported that satisfaction applied to the contact with the geriatrician within an in-patient CGA program, but it also appeared concurrently with a lack of understanding regarding the meaning of the intervention [25]. For out-patient CGA programs both with and without subsequent interventions, the discrepancy between satisfaction and efficacy has been underlined before [26]. It is also noted in other settings, like residential care [27] and within the concept of person-centred care [28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to our findings, Darby et al reported that satisfaction applied to the contact with the geriatrician within an in-patient CGA program, but it also appeared concurrently with a lack of understanding regarding the meaning of the intervention [25]. For out-patient CGA programs both with and without subsequent interventions, the discrepancy between satisfaction and efficacy has been underlined before [26]. It is also noted in other settings, like residential care [27] and within the concept of person-centred care [28].…”
Section: Discussionsupporting
confidence: 87%
“…Kagan et al demonstrated that a lower integration within primary care is linked to lower adherence to recommendations [47]. An explanation for this connection could be that GP need support in acting upon CGA recommendations [26]. Despite the overwhelming amount of literature about the importance of integration of care and the difficulty of implementing this collaborative way of working [48] there is still not enough attention to embedding in existing care or to the context in which outpatient programs are carried out [9].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review, CGAs based on primary care practice were acceptable to the individuals involved but had an inconsistent impact on mortality, functional status and hospital admission rates [4]. Moreover, there is a need for new models that address the complexity of care of older adults living with multimorbidity or frailty in primary care, as these models can lead to quality of care improvements without increases in costs [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…To assess reliability, we included 52 participants, 63.5% female and 69% white, with a median age of 72 years (85-64) and a median schooling duration of 11 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) years. The median AMPI-AB score was 5 (3)(4)(5)(6)(7)(8). The mean time taken to complete the AMPI-AB was 05:44 ± 02:42 min.…”
Section: Reliability and Time To Complete The Instrumentmentioning
confidence: 99%
“…It has been discussed by many in the past without leading to sustained changes in practice [8, 9]. Press identifies that one of the issues may be the nature of PCPs’ relationships with their patients.…”
Section: Introductionmentioning
confidence: 99%